Phenotypic and Genotypic Correlations between Each Pair of Rice Characters under Yellow Orange Leaf Virus Infection - Boonhong Chongkid; Chairerg Maneephong; Narong Singburaudom; Watchara Purivirojkul (Agriculture and Natural Resources, 1992)
Eight rice varieties, ARC11554, GS10719, Suphan Buri 60 (SPR 60), RD9, RD1, RD23, RD7 and TN1 in addition to their 28 F1 s obtained from the diallel crossing among the 8 parents were evaluated for reaction to the yellow orange leaf virus infection based on percent leaf yellowing, plant height, number of panicle bearing tillers, and grain yield per plant. ARC11554 and GS10719 are classified as resistant, SPR60 and RD9 as moderately resistant, RD1 and RD23 as moderately susceptible, and RD7 and TN1 as susceptible Phenotypic correlations between each pair of characters were estimated using method described by Griffing (1956). The results showed that percent leaf yellowing was negatively correlated with plant height, number of panicle bearing tillers, and grain yield per plant.